EVALUATION OF ANTI-INFLAMMATORY EFFICACY OF ASCORBIC ACID AFTER THIRD MOLAR SURGERY - Maryam Fatima; Kulsoom Farhat; Shabana Ali; Mudassar Noor; Chaudhary Muhammad Usman; Fauzia Fatima Gilani (Journal of Ayub Medical College Abbottabad, 2023)
Background: Abstraction of wisdom teeth or impacted third molar under local anaesthesia is one of the most frequent interventions by an oral and maxillofacial surgeon. The abstraction of the third molar is usually followed by the release of liberation and consequent trismus, pain, and swelling due to the area of the third molar being highly vascularized and rich in loose connective tissue. objective of the study was to evaluate the anti-inflammatory effect of ascorbic acid following surgical extraction of the third molar. Methods: The current study was carried out Armed Forces Institute of Dentistry, Rawalpindi, from October to December 2022. This was a cross-sectional observational study. Fifty participants who required surgical extraction of the impacted third molar were included in the study via non-probability purposive sampling and were segregated equally into two groups, i.e., Group A and Group B, comprising twenty-five participants in each group. Group A received amoxicillin with clavulanic acid (625 mg) thrice a day and metronidazole (400 mg) twice daily. In comparison, Group B received amoxicillin with clavulanic acid (625 mg) thrice daily, ascorbic acid (500 mg) twice daily, and metronidazole (400 mg) twice daily. Both groups received naproxen sodium as per requirement (550 mg). Pain, facial swelling, and C reactive protein concentration were evaluated until the 7th postoperative day. Results: There was a reduction in pain and facial swelling in both groups, but in the ascorbic acid group, there was more reduction in pain and facial swelling compared to the control group. However, the difference between the two groups in reducing pain and facial swelling was statistically significant (p<0.01). There was a reduction in CRP in both groups, but in the ascorbic acid group, there was more reduction in CRP 2.35 (1.60-5.30) compared to the control group 2.6 (0.86-5.03). However, the difference between the two groups in reducing C reactive protein concentration was statistically insignificant (p>0.05). Conclusion: Our study concluded that ascorbic acid significantly reduced inflammation and C reactive protein, so ascorbic acid should be used as an adjuvant supplement with other conventional drugs.